2011
DOI: 10.1007/s11095-011-0578-3
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Absorption of Monoclonal Antibodies: Role of Dose, Site of Injection, and Injection Volume on Rituximab Pharmacokinetics in Rats

Abstract: The anatomical site of subcutaneous injection influences the rate of absorption and bioavailability of rituximab in rats. Saturable binding may be a major determinant of the nonlinear absorptive transport of monoclonal antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 47 publications
4
98
0
1
Order By: Relevance
“…We systematically investigated several factors that influence absorption behavior of rituximab in rats (Kagan et al, 2012). The anatomic site of injection had a major impact on both the rate and extent of absorption, which is consistent with pharmacokinetic studies for other proteins (Beshyah et al, 1991;Macdougall et al, 1991;Kota et al, 2007).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…We systematically investigated several factors that influence absorption behavior of rituximab in rats (Kagan et al, 2012). The anatomic site of injection had a major impact on both the rate and extent of absorption, which is consistent with pharmacokinetic studies for other proteins (Beshyah et al, 1991;Macdougall et al, 1991;Kota et al, 2007).…”
Section: Introductionsupporting
confidence: 63%
“…A sandwich enzyme-linked immunosorbent assay was used to quantify rituximab concentrations in rat serum samples, as described previously (Kagan et al, 2012). Briefly, rat anti-rituximab IgG2a (clone MB2A4; AbD Serotec, Raleigh, NC) and goat anti-human IgG-peroxidase conjugate (Fc specific; Sigma-Aldrich, St. Louis, MO) were used as capturing and detection antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…49,58,59 Primary pathways for systemic absorption include convective transport of antibody through lymphatic vessels and into the blood, and diffusion of antibody across blood vessels distributed near the site of injection; however, on the basis of its molecular size, it is considered more likely that the RTX administered via s.c. injection is absorbed mainly via convection through lymphatic vessels. [59][60][61] Indeed the lymphatic capillaries are densely distributed in the subcutaneous tissue and their relatively "open" structure facilitates the absorption of the antibody (a macromolecule) from the interstitial space into the lymph. Generally, after s.c. injection, absorption occurs slowly and the time to reach maximum plasma concentration varies from 2 to 8 d. The bioavailability is determined by the extent to which the drug after s.c. administration undergoes pre-systemic catabolism and systemic absorption.…”
Section: -34mentioning
confidence: 99%
“…In this respect, engineered improvements in the FcRn interaction may appear invisible to other biochemical/biophysical properties or physiological processes that govern absorption from the site. 15,16,19 In particular, several studies have demonstrated that the anatomical site of a subcutaneous injection can influence the bioavailability and rate of absorption of protein drugs, 19 thus further examination of different injection sites with Fc mutant mAbs is an important consideration for future work. The preponderance/contribution of the FcRn interaction in the subcutaneous space could also possibly be dissected by studying the relative bioavailability of a mAb engineered to lose complete pH-dependent receptor binding, as in the Abdeg 1,20 interaction, which has been previously described.…”
Section: Mab:fcrn Binding Affinity Measurements With Surface Plasmon mentioning
confidence: 99%